2010
DOI: 10.1111/igc.0b013e3181ef8deb
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Leukocyte Alterations Are Associated With Invasive Uterine Cervical Cancer

Abstract: Patients with advanced cervical cancer had significantly higher frequency of leukocyte alterations, although they may occur apart from the preinvasive stages. Overall, neutrophilia was the best indicator of cancer invasiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 30 publications
1
53
1
2
Order By: Relevance
“…A correlation between the increase of NLR and endometrial cancer invasiveness has been demonstrated (Acmaz et al, 2014). There was an association between NLR and cervical cancer invasiveness in another study (Tavares-Murta et al, 2010). Similarly, in the current study, NLR was higher in the cervical cancer group compared to the preinvasive group.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A correlation between the increase of NLR and endometrial cancer invasiveness has been demonstrated (Acmaz et al, 2014). There was an association between NLR and cervical cancer invasiveness in another study (Tavares-Murta et al, 2010). Similarly, in the current study, NLR was higher in the cervical cancer group compared to the preinvasive group.…”
Section: Discussionsupporting
confidence: 77%
“…The authors have demonstrated that leukocytosis is a risk and prognostic factor in both cancers. The association between leukocytosis and the stage of cervical cancer was demonstrated in another study (Tavares-Murta et al, 2010). The authors concluded that leukocytosis is closely associated with tumor stage.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, neutrophil and lymphocyte counts were elevated and reduced respectively in advanced stage uterine cervical cancer. 93 Martin 94 suggested that definitive analyses require specific methodologies to account for shifts in cellular population heterogeneity.…”
Section: Overall Summarymentioning
confidence: 99%
“…6 Macrophage infiltration into cervical tumours has been positively correlated with tumour vascularity 18 and women with advanced-stage invasive cancer have higher blood neutrophil counts than those with early-stage disease. 19 Although the precise mechanism for immune cell recruitment into the cervix in humans has not been elucidated, prostaglandins biosynthesised by COX enzymes in epithelial, stromal and vascular cells have been shown to induce the expression of a host of cytokines and chemokines. These can in turn act in an autocrine or paracrine manner in the cervix to enhance inflammation by promoting tissue remodelling and recruitment of immune cells via chemotaxis and extravasation, which in turn can promote disease progression.…”
Section: Regulation Of Vascular Function and Immune Cell Recruitment mentioning
confidence: 99%